The Spirit of Philadelphia : A Call to Recover the Founding Principles - Gibson, Christopher P. (Routledge, Taylor & Francis Group, 2025)
The Spirit of Philadelphia is America's story told through the history of ideas and a cautionary tale of what happens when a nation's Spirit goes dormant.This book proposes a return of the American government to the philosophical roots as articulated by the U.S. Constitution and its Framers. Grounded in realism, the Founders successfully balanced the needs and rights of the individual with those of the collective, creating a system that prioritized both personal liberty and societal order. Author and former Congressman Chris Gibson argues that abandoning the "Spirit of Philadelphia" (essentially the national spirit of cooperation, compromise, and teamwork) enabled dysfunction in government and disillusionment in the constituency. Culminating a comprehensive list of policy recommendations that logically analyze issues in the American political system, the author proposes an agenda aimed at restoring faith and functionality in national institutions and leaders, fostering bipartisan communication and collaboration, and revitalizing civic engagement at the individual level.Illustrating the changes in the political landscape of America since the Philadelphia convention, this book is an important read for students of democracy, political participation, elections, and voter behavior.